2011
DOI: 10.1371/journal.pone.0019520
|View full text |Cite
|
Sign up to set email alerts
|

Red Fluorescent Protein-Aequorin Fusions as Improved Bioluminescent Ca2+ Reporters in Single Cells and Mice

Abstract: Bioluminescence recording of Ca2+ signals with the photoprotein aequorin does not require radiative energy input and can be measured with a low background and good temporal resolution. Shifting aequorin emission to longer wavelengths occurs naturally in the jellyfish Aequorea victoria by bioluminescence resonance energy transfer (BRET) to the green fluorescent protein (GFP). This process has been reproduced in the molecular fusions GFP-aequorin and monomeric red fluorescent protein (mRFP)-aequorin, but the lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 43 publications
0
49
0
Order By: Relevance
“…On the other hand, given the recent expansion of hues in fluorescent proteins (Shaner et al, 2004), future efforts will focus on the engineering of GAP variants with different colors (cyan, yellow, orange, or red) that enable simultaneous imaging of Ca 2+ in various locations. Fusions of aequorin to red fluorescent proteins such as mRFP1 (Manjarres et al, 2008) or tdtomato (Bakayan et al, 2011) have been previously reported as bioluminescent sensors. Substitution of the GFP moiety of GAP for mRFP1 rendered a protein insensitive to calcium (P.N.-N., unpublished data).…”
Section: In Vivo Monitoring Of Ca 2+ Release In the Sarcoplasmic Retimentioning
confidence: 99%
“…On the other hand, given the recent expansion of hues in fluorescent proteins (Shaner et al, 2004), future efforts will focus on the engineering of GAP variants with different colors (cyan, yellow, orange, or red) that enable simultaneous imaging of Ca 2+ in various locations. Fusions of aequorin to red fluorescent proteins such as mRFP1 (Manjarres et al, 2008) or tdtomato (Bakayan et al, 2011) have been previously reported as bioluminescent sensors. Substitution of the GFP moiety of GAP for mRFP1 rendered a protein insensitive to calcium (P.N.-N., unpublished data).…”
Section: In Vivo Monitoring Of Ca 2+ Release In the Sarcoplasmic Retimentioning
confidence: 99%
“…Due to the presence and proximity of both GFP and aequorin inside the jellyfish, the blue light, which is emitted by aequorin as the donor molecule is transferred to GFP as the acceptor molecule via BRET phenomenon, and it results in a change in the emission wavelength to green. Based on this natural model, researchers design different BRET systems in which some fluorescent proteins [35,37,38] or chromophores [36,39] are used as energy accepters. In this study, aequorin is modified through attaching quantum dots (QDs) nanoparticles to it in order to achieve the longer emission wavelength.…”
Section: Resultsmentioning
confidence: 99%
“…In these systems, photoprotein acts as a donor, whereas fluorescent proteins [35,37,38], fluorophores [36,39] can act as acceptors. One of the surprising synthetic fluorescent molecules, which acts as the BRET acceptor is QDs [40][41][42][43].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, detection of OH-PCBs in physiological samples may serve as a means of evaluating exposure to PCBs. Furthermore, OH-PCBs, although less toxic than PCBs, have significant adverse health effects, given that they can act as endocrine disruptors [37] and increase the formation of reactive oxygen species [1]. This emphasizes the importance of OH-PCB detection in physiological samples.…”
Section: Hydroxylated Polychlorinated Biphenylsmentioning
confidence: 99%
“…Mercury can exist in three major forms, elemental, inorganic, and organic. Approximately 80% of mercury released from human activities is in the elemental form [37]. Dental amalgams contain 50% mercury, with silver, tin, and copper [40].…”
Section: Mercury(ii) Ionsmentioning
confidence: 99%